Review of issues and challenges in the growing use of herbal-based products - Rajendran, Salini Devi; Kamarulzaman, Nitty Hirawaty (Universiti Teknologi Mara Press, 2023)
Since the beginning of human life, herbs have been an integral part of society, with both dietary and therapeutic values recognised. Natural ingredients are increasingly used as key ingredients in food product preparation. The food system and its effects have encouraged people to use natural resources to provide a wide range of nutritional products and good quality healthy foods. A recent consumption pattern among Malaysians on herbal-based food products shows an upward trend indicating that they are looking for healthy, safe, and natural products. The herbal-based products continue to be accepted and supported by the locals for their health and illness treatment. This has led to a rise in the popularity of herbal-based products in Malaysia. However, because safety remains the primary concern with using herbal-based products, relevant regulatory authorities must implement appropriate measures to protect public health by ensuring that all herbal-based products are safe to consume and of the right quality. This review highlights herbal-based product issues, major safety concerns associated with consuming herbal products, and significant challenges associated with effective safety and quality monitoring.